Lessons learned from youth-engaged research methods to conduct qualitative analysis with a transgender and gender-diverse youth advisory board - An H. Pham; Zoe Webster; Melanie K. Bean; Suzanne Mazzeo; Kym Ahrens; Maria Thomson (PLoS ONE, 2026)
Although community-engaged research is becoming more common, youth-engaged research methods, particularly its application to qualitative analysis, remains rare. The Research on Identity Specific Eating Disorder Symptoms (RISES) Project developed, partnered with, and maintained a youth advisory board of five transgender, non-binary, and gender-diverse youth in all stages of a qualitative study, including qualitative analysis. Youth advisory board members contributed to a codebook, coded two to six transcripts each, provided feedback on themes and supporting quotes, and authored this paper. After one year, we achieved a retention rate of 83.3% of all youth advisory board members, and 100% of youth advisory board members trained in qualitative analysis. This paper describes the lessons learned from partnering with and training a transgender, non-binary, and gender-diverse youth advisory board to conduct qualitative analysis.